2022
DOI: 10.3390/molecules27206839
|View full text |Cite
|
Sign up to set email alerts
|

Toxicological Assessment of Roasted Coffee Silver Skin (Testa of Coffea sp.) as Novel Food Ingredient

Abstract: Roasted coffee silver skin is a coffee by-product, the uses of which are currently limited, e.g., as fertilizer, for energy production, or animal feed. Due to a low content of fat and carbohydrates combined with a high content of fiber, polyphenols and proteins, roasted silver skin is a valuable possible food ingredient. Potential applications include partial flour replacement in bakery products, as antioxidant and providing protein or fiber sources in sports or functional foods. As no relevant consumption of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 84 publications
0
2
0
Order By: Relevance
“…However, CS has been classified as a novel food (category: "Foodstuffs from plants or parts of plants") [48] according to Regulation (EU) 2015/2283 on novel foods [49], thus requiring pre-market authorization, released by the European Food Safety Authority (EFSA). Moreover, several contaminants can be found in CS [36], such as ochratoxin A, which was detected at concentrations of up to 34.4 µg/kg, well above the 5 µg/kg limit established by Regulation (EC) No. 1881/2006 [50] for coffee and cereals [36,[51][52][53].…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, CS has been classified as a novel food (category: "Foodstuffs from plants or parts of plants") [48] according to Regulation (EU) 2015/2283 on novel foods [49], thus requiring pre-market authorization, released by the European Food Safety Authority (EFSA). Moreover, several contaminants can be found in CS [36], such as ochratoxin A, which was detected at concentrations of up to 34.4 µg/kg, well above the 5 µg/kg limit established by Regulation (EC) No. 1881/2006 [50] for coffee and cereals [36,[51][52][53].…”
Section: Introductionmentioning
confidence: 85%
“…Moreover, several contaminants can be found in CS [36], such as ochratoxin A, which was detected at concentrations of up to 34.4 µg/kg, well above the 5 µg/kg limit established by Regulation (EC) No. 1881/2006 [50] for coffee and cereals [36,[51][52][53]. In addition, aflatoxins concentrations were found safe only for food not intended for children or for medical purposes [36,54].…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Another study determined the pH value of silverskin aqueous extract as an average value for both Coffea arabica and Coffea canephora at 5.00. A possible explanation for this might be the different origins of the analyzed samples in the given study [36].…”
Section: Phmentioning
confidence: 93%
“…Rodriguez et al [54] reported a similar fiber content in silverskin (56-62%). However, Loorbeer et al [36] reported a much wider range (34.70-68.50%).…”
Section: Fiber Contentmentioning
confidence: 94%